2015
DOI: 10.1038/srep10836
|View full text |Cite
|
Sign up to set email alerts
|

Nodulation Characterization and Proteomic Profiling of Bradyrhizobium liaoningense CCBAU05525 in Response to Water-Soluble Humic Materials

Abstract: The lignite biodegradation procedure to produce water-soluble humic materials (WSHM) with a Penicillium stain was established by previous studies in our laboratory. This study researched the effects of WSHM on the growth of Bradyrhizobium liaoningense CCBAU05525 and its nodulation on soybean. Results showed that WSHM enhanced the cell density of CCBAU05525 in culture, and increased the nodule number, nodule fresh weight and nitrogenase activity of the inoculated soybean plants. Then the chemical compounds of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 44 publications
3
46
0
Order By: Relevance
“…These results indicate that adding FAs to liquid cultures can increase growth of S. meliloti , with a similar result demonstrated in a study comparing the presence of a HS substance with no addition ( Xu et al , 2018 ). Furthermore, the effect of FAs on increasing microbial cell growth without the presence of a plant interaction agrees with other published studies; HS addition has been shown to increase growth of Bradyrhizobium liaoningense in liquid culture ( Guo Gao et al , 2015 ) and increase general microbial population growth in soil microbial cells ( Visser, 1985 ). In contrast, a study of Candida utilis found no growth change with HS application, so the response may be specific to certain taxa ( McLoughlin and Küster, 1972 ).…”
Section: Resultssupporting
confidence: 91%
“…These results indicate that adding FAs to liquid cultures can increase growth of S. meliloti , with a similar result demonstrated in a study comparing the presence of a HS substance with no addition ( Xu et al , 2018 ). Furthermore, the effect of FAs on increasing microbial cell growth without the presence of a plant interaction agrees with other published studies; HS addition has been shown to increase growth of Bradyrhizobium liaoningense in liquid culture ( Guo Gao et al , 2015 ) and increase general microbial population growth in soil microbial cells ( Visser, 1985 ). In contrast, a study of Candida utilis found no growth change with HS application, so the response may be specific to certain taxa ( McLoughlin and Küster, 1972 ).…”
Section: Resultssupporting
confidence: 91%
“…Humate acted as a bio-stimulant affecting both microbial diversity and function of both fungal www.nature.com/scientificreports www.nature.com/scientificreports/ and bacterial taxa. Humic substances have previously been shown to affect rhizosphere microbial populations [63][64][65] and humate may act similarly to humic extracts known to increase legume nodulation and nitrogenase activity, stimulate nod gene expression, cell metabolism and nutrient transport 66 . Another possible mode of action is through stimulation of microbial production of plant growth regulators such as auxins, cytokinins or abscisic acid if the appropriate humic precursors are present in populations [67][68][69] .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, comparative proteomic studies have been used in the identification of putative symbiotic genes (Gomes et al 2012b). Several processes of more direct relevance to SNF have also been studied using proteomics (Table 3), such as the proteomic response to flavonoids (Guerreiro et al 1997;Chen et al 2000b;Hempel et al 2009;da Silva Batista and Hungria 2012;Arrigoni et al 2013;Tolin et al 2013;Gao et al 2015;Meneses et al 2017); and to micro-aerobic or anaerobic conditions (Dainese-Hatt et al 1999). The secretome of rhizobia, with a particular focus on the proteins exported by type III secretion systems, has also been investigated (Saad et al 2005;Rodrigues et al 2007;Hempel et al 2009;Okazaki et al 2009).…”
Section: Proteome Studies Of Rhizobiamentioning
confidence: 99%